Ingrown Toenail in Children and Conservative Treatment Methods: A Case Report - Jakubczak, Michalina; Mazurek, Klaudia; Wcisło‐Dziadecka, Dominika (Journal of cosmetic dermatology, 2025)
ABSTRACT Background Ingrown toenails are a disease that often begins in childhood. It occurs as the penetration of the nail plate into the surrounding tissue as a result of various factors. Patients often report to various specialists, including podiatrists and dermatologists, at an advanced stage of this disease. Aims The aim of the study is to present the effectiveness of conservative treatment methods in children with ingrown toenails. Methods In this study, we presented the case of a 12‐year‐old boy with ingrown toenails and visible inflammation around the toenails of both feet. Taking into account Scholz's classification, the severity of the disease in the right foot was assessed as 3B, and in the left foot as 3A. Non‐surgical conservative methods were used, such as cutting the wedge of the nail apparatus, applying a tamponade and implementing orthonyxia methods, which gave a quick therapeutic effect and the disappearance of unpleasant pain symptoms. Results Conservative treatment methods using orthonyxia are highly effective, even in advanced stages of ingrowing nail plate. Medical procedures using conservative treatment techniques allow for quick help for pediatric patients in a safe manner and with a low risk of complications. Conclusions Ingrown toenails can occur at any age, often including childhood, and conservative treatment methods should be the first possible treatment option.